Faktor yang Berhubungan dengan Kadar Hemoglobin Pada Petani Bawang Merah - Susilowati, Devi Ayu; Muzayanah, Siti (Indonesian Journal of Health Community, 2021)
Activities in the agricultural sector cannot be separated from the use of pesticides to prevent agricultural products from pests. The use of pesticides that are at risk can cause abnormalities in the blood profile. This study aims to determine the factors associated with hemoglobin levels in farmers exposed to pesticides in Tegalglagah Village, Brebes Regency. This study used a cross sectional design. Sampling with a total sampling of 42 people, venous blood sampling to determine the hemoglobn level of respondents using the Cyanmethemoglobin method. The results showed that most of the respondents who were exposed to pesticides were normal (52.38%), most of the respondents smoked while spraying pesticides (73.80%), most of them used Personal Protective Equipment (PPE) while spraying (52.38%) ), and most of them sprayed <4 hours per day (59.52%), the factors related to hemoglobin levels were the use of PPE when spraying with a p-value of 0.013 and length of work per day with a p-value of 0.032. It was concluded that the use of PPE when spraying and the length of work per day were related to hemoglobin levels.